Kristiawan, Purnomo Membangun Surga Yang Hilang: Pengelolaan Objek Wisata Air Terjun Jumog Ditinjau dari Prinsip Wirausaha Lestari dan Etika Global - Purnomo Kristiawan (Melo: Jurnal Studi Agama-agama, 2023)
Abstract: Tourism has a considerable impact on the people of Karanganyar, as the Jumog waterfall has created new jobs and economic growth for the people of Berjo. On the other hand, this growth in the tourism sector also raises ecological, sociological and even theological problems that cause some local residents to not be able to enjoy the results of Jumog waterfall tourism but instead get the impact of environmental damage caused by investors. This research aims to examine the issue of Jumog waterfall from the perspective of sustainable entrepreneurship based on three fundamental things, namely justice, welfare and sustainability. This paper uses a qualitative research method that utilizes a literature study of the main literature from the thoughts of Emanuel Gerrit Singgih on ecological theology and Yahya Wijaya on the concept of sustainable entrepreneurship with the dimensions of Profitability, Solidarity and Sustainability. In this paper, it is found that to improve and advance the management of Jumog waterfall tourist attractions, efforts are needed to turn the haunted into the sinengker by building an internalized theology of panentheism through village clean rituals, caring for local wisdom such as the value of mutual cooperation and tribrata learning from RM Said and the need to empower the berjo village community through systematically designed trainings to improve competence in management  Jumog waterfall attraction. Abstrak: Pariwisata memberi dampak yang cukup besar bagi masyarakat Karanganyar, sebagaimana air terjun Jumog yang telah menciptakan lapangan kerja baru dan pertumbuhan ekonomi bagi masyarakat Berjo. Di lain sisi, pertumbuhan di sektor pariwisata ini menimbulkan persoalan ekologis, sosiologis bahkan teologis yang menyebabkan beberapa warga lokal tidak dapat menikmati hasil dari wisata air terjun Jumog. Namun, justru mendapatkan dampak dari kerusakan lingkungan yang disebabkan oleh investor. Penelitian ini hendak mengkaji persoalan air terjun Jumog dari perspektif kewirausahaan lestari yang berbasis pada tiga hal mendasar, yakni keadilan, kesejahteraan dan keberlanjutan. Tulisan ini menggunakan metode penelitian kualitatif yang memanfaatkan studi pustaka atas literatur utama dari pemikiran Emanuel Gerrit Singgih mengenai teologi ekologi dan Yahya Wijaya tentang konsep kewirausahaan lestari yang berdimensi profitabilitas, solidaritas dan keberlanjutan. Tulisan ini menemukan bahwa untuk meningkatkan dan memajukan pengelolaan objek wisata air terjun Jumog diperlukan upaya mengubah yang angker menjadi yang sinengker dengan membangun teologi panenteisme yang diinternalisasi melalui ritual bersih desa dan merawat kearifan lokal seperti nilai kegotong-royongan.